Differences in physical fitness profiles of athletes in cyclic activities (running, cycling, biathlon) - Pavlovic, R.; Vrcic, M.; Radulovic, N. (European Journal of Physical Education and Sport Science, 2023)
Endurance-type disciplines (running, cycling, biathlon) define the cyclic structure of an athlete's movements, which, in addition to functional parameters, also includes an adequate fitness profile. Based on the detection, analysis and evaluation of these parameters, it is possible to define the fitness profile of the competitors as well as possible mutual differences. The current case study analyzes the fitness profile of competitors of three different disciplines (middle and long distances, cycling, ski biathlon) of top-level competitors, members of national teams. The study was conducted: Uroš Gutic (UG) - runner middle and long distances, member of AK "Sarajevo" and the BIH athletic national team; Milan Milivojevic (MM) - cyclist, member of Cycling club "Borac" Cacak (Serbia), and the member Serbian national team; Stefan Lopatic (SL) - ski biathlete, member SK "Romanija" Pale, and BIH national team. A total of 12 parameters were measured to assess the fitness profile (repetitive strength, explosive strength, speed and agility). The results recorded considerable homogeneity of the sample with mutual differences. In addition to mutual differences, all study participants are characterized by an extremely good fitness profile, as shown by the measurement results.